(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with what is motivation (you can learn external motivation and internal motivation as well as some techniques with a bit more power), the importance of motivation, why do we need a motivation in our life (you will witness the real-life experience, its benefit and result in my future, as well as, some quotes said by celebrities). It is no secret that, motivation is an integral part of our life that can lead us to a large number of achievements. It also opens every door easily along the way when we have a lot on our mind.